Fusion Burn Regulation via Deuterium Tritium Mixture Control in the Joint European Torus - M. Lennholm; L. Piron; D. Valcarcel; P. Almond; M. Baruzzo; M. van Berkel; T. Bosman; L. Ceelen; P. Fox; K. Kirov; B. Kool; C. Lowry; et al. (PRX Energy)
The first generation of nuclear fusion reactors is expected to operate using a mixture of deuterium (D) and tritium (T) fuel. Controlling the D:T ratio is a promising option to control the fusion burn rate. The Joint European Torus (JET), as the only operational tokamak that can use tritium, is uniquely placed to test the feasibility of such control. Experiments carried out in 2023, during the third JET D-T campaign, have demonstrated effective feedback control of the D:T ratio under H-mode conditions. The D:T ratio was measured using visible spectroscopy and tritium was injected via gas valves, while deuterium was injected either via gas valves or pellets. In these experiments, the fusion power, measured via the neutron rate, responded promptly to variations in the measured D:T ratio. This demonstrates that, although the plasma is fueled mainly at the edge, rapid mixing of the isotopes occurs throughout the plasma and controlling the D:T ratio is an effective way of controlling the burn rate. To sustain a stable type-I ELMy H-mode plasma, it is desirable to maintain a given edge localised mode (ELM) frequency. However, both the total fueling rate and the D:T ratio influence this ELM frequency, with higher fueling rates and higher D:T ratios both resulting in more frequent ELMs. For this reason, the D:T ratio controller was combined with an ELM frequency controller in a multi-input multi-output controller. Successful simultaneous decoupled control of the D:T ratio and ELM frequency was demonstrated using a combination of pellet and gas fueling. This is the first and, for the time being, only demonstration of such an advanced burn control scheme in a DT plasma.